2018
DOI: 10.20944/preprints201810.0351.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ionic Liquid-Promoted Three-Component Domino Reaction of Propargyl Alcohols, Carbon Dioxide and 2-Aminoethanols: A Thermodynamically Favorable Synthesis of 2-Oxazolidinones

Abstract: To circumvent the thermodynamic limitation of the synthesis of oxazolidinones starting from 2-aminoethanols and CO2 and realize incorporation CO2 under atmospheric pressure, a protic ionic liquid-facilitated three-component reaction of propargyl alcohols, CO2 and 2-aminoethanols was developed to produce 2-oxazolidinones along with equal amount of α-hydroxyl ketones. The ionic liquid structure, reaction temperature and reaction time were in detail investigated. And 15 mol% [TBDH][TFE] (1,5,7-triazabic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…25 He and co-workers reported that [HTBD][TFE] could catalyze the reaction of propargylic alcohols with atmospheric CO 2 and 2-aminoethanol through synergistically activating the substrates and CO 2 , affording a wide range of 2-oxazolidinones along with an equal amount of α-hydroxyl ketones. 26 2.1.4. Carbonylation of o-Phenylenediamines with CO 2 .…”
Section: We Discovered That [Hdbu] + -Based Protic Ils Such As [Hdbu]...mentioning
confidence: 99%
“…25 He and co-workers reported that [HTBD][TFE] could catalyze the reaction of propargylic alcohols with atmospheric CO 2 and 2-aminoethanol through synergistically activating the substrates and CO 2 , affording a wide range of 2-oxazolidinones along with an equal amount of α-hydroxyl ketones. 26 2.1.4. Carbonylation of o-Phenylenediamines with CO 2 .…”
Section: We Discovered That [Hdbu] + -Based Protic Ils Such As [Hdbu]...mentioning
confidence: 99%